Flavonoids as Aglycones in Retaining Glycosidase-Catalyzed Reactions: Prospects for Green Chemistry - Kotik, Michael; Kulik, Natalia; Valentová, Kateřina (Journal of agricultural and food chemistry, 2023)
Flavonoids and their glycosides are abundant in many plant-based foods. The (de)glycosylation of flavonoids by retaining glycoside hydrolases has recently attracted much interest in basic and applied research, including the possibility of altering the glycosylation pattern of flavonoids. Research in this area is driven by significant differences in physicochemical, organoleptic, and bioactive properties between flavonoid aglycones and their glycosylated counterparts. While many flavonoid glycosides are present in nature at low levels, some occur in substantial quantities, making them readily available low-cost glycosyl donors for transglycosylations. Retaining glycosidases can be used to synthesize natural and novel glycosides, which serve as standards for bioactivity experiments and analyses, using flavonoid glycosides as glycosyl donors. Engineered glycosidases also prove valuable for the synthesis of flavonoid glycosides using chemically synthesized activated glycosyl donors. This review outlines the bioactivities of flavonoids and their glycosides and highlights the applications of retaining glycosidases in the context of flavonoid glycosides, acting as substrates, products, or glycosyl donors in deglycosylation or transglycosylation reactions.
Keywords: Transglycosylation; Catalysis; Glycoside hydrolase; Rutinosidase; Glycosides; Glucosidase; Glycosyl donor; Flavonoids; Glycosynthase; glykosylace; glykosidhydrolasy; Glycosylation; flavonoidy; Glycoside Hydrolases; glykosidy; katalýza; Hydrolysis